Potensi Manfaat Kardioprotektif dari Minyak Zaitun - Anisa Prima Justica Mustikyantoro (Jurnal Ilmiah Kesehatan Sandi Husada, 2020)
Cardiovascular disease is the leading cause of death in the world and the two main risk factors for its development are aging and diet. Diet plays a decisive role in health maintenance and disease prevention. Meanwhile, olive oil is known to provide beneficial effects on hypertension and the prevention of cardiovascular disease with various important components in it. There are two types of olive oil depending on the production mechanism, namely extra virgin olive oil (EVOO) and refined olive oil (ROO). This literature study aimed to assess the association between olive oil intake and the risk of cardiovascular disease and the potential cardioprotective benefits of olive oil. Method. This research is a literature review involving 18 literature sources from 1 national journal and 17 international journals. Result. Several studies have significantly demonstrated the cardioprotective, antithrombotic, and anti-inflammatory properties of olive oil from both the major and minor components of olive oil. Conclusion. Consistent food intake with olive oil can provide a cardioprotective effect from various important components in it, as a prevention of cardiovascular disease.